Developments and challenges in dermatology: an update from the Interactive Derma Academy (IDeA) 2019. (14th December 2020) - Luger, T.; Dirschka, T.; Eyerich, K.; Gollnick, H.; Gupta, G.; Lambert, J.; Micali, G.; Ochsendorf, F.; Ständer, S.; Traidl‐Hoffmann, C.
Abstract: The 2019 Interactive Derma Academy (IDeA) meeting was held in Lisbon, Portugal, 10–12 May, bringing together leading dermatology experts from across Europe, the Middle East and Asia. Over three days, the latest developments and challenges in relation to the pathophysiology, diagnosis, evaluation and management of dermatological conditions were presented, with a particular focus on acne, atopic dermatitis (AD) and actinic keratosis (AK). Interesting clinical case studies relating to these key topics were discussed with attendees to establish current evidence‐based best practices. Presentations reviewed current treatments, potential therapeutic approaches and key considerations in the management of acne, AK and AD, and discussed the importance of the microbiome in these conditions, as well as the provision of patient education/support. It was highlighted that active treatment is not always required for AK, depending on patient preferences and clinical circumstances. In addition to presentations, two interactive workshops on the diagnosis and treatment of sexually transmitted infections/diseases (STIs/STDs) presenting to the dermatology clinic, and current and future dermocosmetics were conducted. The potential for misdiagnosis of STIs/STDs was discussed, with dermoscopy and/or reflectance confocal microscopy suggested as useful diagnostic techniques. In addition, botulinum toxin was introduced as a potential dermocosmetic, and the possibility of microbiome alteration in the treatment of dermatological conditions emphasized. Furthermore, several challenges in dermatology, including the use of lasers, the complexity of atopic dermatitis, wound care, use of biosimilars and application of non‐invasive techniques in skin cancer diagnosis were reviewed. In this supplement, we provide an overview of the presentations and discussions from the fourth successful IDeA meeting, summarizing the key insights shared by dermatologists from across the globe.